PENINGKATAN KUALITAS PELAYANAN PUBLIK MELALUI PEMBAYARAN REKENING AIR SECARA ONLINE PADA PERUSAHAAN DAERAH AIR MINUM KABUPATEN BOJONEGORO - Niken Ayu Febrianti; Hayat; Agus Zainal Abidin (Journal Publicuho, 2023)
This study discusses improving the quality of service by using online water payments at regional drinking water companies in Bojonegoro Regency. This research is based on problems related to service quality that is not optimal. The purpose of this study was to determine the use of information technology for public services and also to find out the supporting factors and inhibiting factors in the application of information technology in PDAM Bojonegoro Regency. This research method uses qualitative research which aims to provide a clear description and understanding of the phenomena studied. The results of this study are that improving service quality through online water bill payments at Local water company Bojonegoro Regency is quite good as assessed by 8 indicators according to Carlson and Schwarz (1995) in Denhardt & Denhardt (2003:61) which include the following: convenience , security, reliability, personal attention, problem solving approach, fairness, fiscal responsibility, citizen influence. In addition, there are supporting factors and inhibiting factors for paying water bills online.